From Theory to Practice: An Adaptive Development of Design Education - I-Ying Chiang; Po-Hsien Lin; John G. Kreifeldt; Rungtai Lin (MDPI AG, 2021)
This study aims to discuss the adaptive challenge, and bridge the gap between theory and practice in design education. From now on, navigating design communities through the new era is a significant issue facing global competition and pluralistic society. First, this study reviews the essential evolution of design theories in the past few decades on man-machine system design, user-centered design, and user experience design. Second, based on three case studies of the REACH toothbrushes, an IEF wearable computer, and a LINNAK twin-cup, the research findings are offered to witness the advancement and transformation from hi-tech to hi-touch. Furthermore, this study summarizes three paradigms to interpret the adaptive evolution in design education. Finally, the authors propose three directions for the advancement of the creative industry and design education. The contributions of this study are to (1) clarify the interrelations between the theory and practice of design via the three foci of the human factors, human actors, and cultural aspects; (2) demonstrate the transformation of the archetypal model of user-tool-task employing illustrative paradigms; (3) identify the evolution of design education with contextual stages in the past decades; and (4) propose orientated perspectives for the personnel and institutes of the design industry and design education.